THE APPLICATION OF LANGUAGE LEARNING STRATEGIES AND THEIR RELATIONSHIP WITH ENGLISH PROFICIENCY OF THE ISLAMIC JUNIOR HIGH SCHOOL STUDENTS AT RADEN PAKU MODERN ISLAMIC BOARDING SCHOOL TRENGGALEK - FRESISKA, FEBRIANA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Nowadays, English is getting more important in Indonesia. Not only as a means of communication with the foreigner but also as one of the subjects in National Examination. Learning English is different from learning Bahasa Indonesia because it has many different aspects of language including grammar, vocabularies and also pronunciation. Then, learning strategies are needed to make the learning easier and faster. This study is conducted in order to investigate the language learning strategies used by Raden Paku Islamic Junior High School students and to investigate the relationship between six categories of language learning strategies and English proficiency.The samples of this study are 114 students consisting of 40 students of 7th grade, 37 students of 8th grade and 37 students of 9th grade. The research instruments are SILL questionnaire and English score. The data obtained from the returned surveys are analyzed using descriptive statistics and Pearson Product Moment correlation.The results shows that the students are medium users of overall strategies with metacognitive strategy as the most frequently used by 7th grade and 8th grade students. Meanwhile, metacognitive and affective strategies are the most frequently used by 9th grade. The lowest strategy is compensation strategy for all grades. The significant correlation was found between Language Learning Strategies and 7th English proficiency but no significant correlation was found in 8th grade and 9th grade.The writer suggests the teachers to promote language learning strategy application to the students especially for memory and affective strategy because they have significant correlation with English proficiency. She also suggests for the next writers to conduct the research in the level of elementary school and correlate language learning strategy with the specific learning skill. Key words: language learning strategies, language proficiency, the Strategy Inventory for Language Learning (SILL).